Die aanwending van ’n kwalitatiewe metodologiese model in gesinsmoordnavorsing: ’n Suid-Afrikaanse gevallestudie - Schurink, W. J. J. (Koers, 1992)
In the light of limited research on family violence and the fact that the phenomenon of family murder has generally not been researched systematically in South Africa, this article provides an exposition of the way in which family murder has been studied qualitatively in a recent HSRC project. In accordance with current views on criteria for evaluating qualitative studies, a natural history of the most important decisions taken during the execution of the research is presented In addition, the article indicates how the study complies with the standards of qualitative research.